Socio-Economic Relationship of Infection Diseases and History of Exclusive ASI with Stunting Incidents - Dayana Noprida; Nyimas Heny P; Anita Apriliawati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Stunting is a condition where a person has a shorter height compared to the height of people of the same age in general. Objectives: This study aims to determine the relationship between socio-economics, infectious diseases, and exclusive breastfeeding with the incidence of stunting in toddlers in the Pringsewu Region, Pringsewu Regency. Methods: The design of this research is observational analytic with a cross-sectional approach. The population is mothers who have children aged 2-5 years in the Pringsewu Lampung Health Center Working Area. Results: The results of the study showed that there was a socio-economic relationship (maternal employment and income), history of infection, and exclusive breastfeeding with the incidence of stunting (p-value <0, 05) after being controlled by the quality of food intake. Conclusion: It is hoped that this research can become evidence-based practice and motivate health officers (nurses) to carry out independent nursing interventions by providing health education to mothers regarding stunting prevention behavior by utilizing posyandu held in the community.